Influence of Dicoumarol Derivatives on Plasma Fibrinolytic System - Niewiarowska, Marta; Wegrzynowicz, Zenon (Thrombosis and Haemostasis, 1959)
The influence of some coumarine derivatives (anticoagulant drugs: pelentan [tromexan], sintrom, marcoumar) on plasma fibrinolytic activity has been investigated. The cases studied included a number of patients with coronary thrombosis treated in long-term anticoagulant therapy and rabbits treated with a single dose of the drug.The anticoagulants have no significant effect either on fibrinogen or plasminogen level. All of the above mentioned drugs cause a prolongation of the euglobulin fibrinolysis time and an increase of the antiplasmin level. These two changes may be correlated to the prolongation of the prothrombin time.The authors suggest that the described phenomena may be useful for biological and clinical evaluation of anticoagulant drugs.